Polarisation beyond the Pandemic? Fissures within the German Public and the Role of Public Theology - Wabel, Thomas (Stellenbosch Theological Journal, 2025)
After some initial background information on the relation of church and state in the German context, the article examines reactions by churches and other Christian groups in Germany to the Covid-19 containment measures. While representatives of mainline churches focussed on consolation in the crisis and support state measures, a minority of radical voices acted in a polarising way, offering interpretations in terms of spiritual warfare, betrayal of the gospel, and conspiracy theories, and regarding themselves as victims of health policy. It is argued that the Christian tradition is in itself ambiguous and can be used in destructive ways, and that clarification of concepts is a task of public theology. The paper concludes by pointing out opportunities for the contribution of religions to a critical assessment of the handling of this crisis in the state and society.